Home- School Link: Tutor’s Capacity-Building Enhancement Training for effective implementation of Modular distance learning - Mamolo, Jessica Normie F.; Kintanar, Fitzgerald C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study discovers the effectiveness of modular distance learning as an alternative learning modality and proposes a home-school link: a tutor’s capacity-building enhancement training. The study examines the perceived level of competence and tutoring experiences of the parents while administering the self-learning modules (SLM) at home. The study determines the relevance of parents’ tutoring competence and experiences to the learner’s academic achievement, which were identified using a mixed-methods approach through conducting both surveys and interviews. The study used a purposive sampling technique to select the participants. This study reveals that parents are only proficient in administering the module, which demonstrates their need to undergo capacity-enhancement training. Facilitating the SLM emphasizes the significance of the delivery of instruction, employing the student-centered method, appropriate teaching strategies, student motivation, behavior management strategies, and time management. In this connection, the training specifically provides opportunities for the home tutors to acquire the knowledge and skills that they need to deliver a high-quality education to the learners. Moreover, this study reveals the different interventions and challenges encountered while administering modular distance learning. Conducting the teaching-learning process at home can be difficult for home tutors who do not possess the necessary competence to facilitate the SLM, which imposes a risk of producing high-quality outcomes in learners' academic achievement. Hence, it is crucial to implement the home-school link: a tutor’s capacity-building enhancement training to nurture the necessary competences of the home tutors as partners in education. Implementing the enhancement training ensures the quality education our learners wholly deserve.